2022
DOI: 10.1002/mp.16136
|View full text |Cite
|
Sign up to set email alerts
|

A contrast‐enhanced MRI‐based nomogram to identify lung metastasis in soft‐tissue sarcoma: A multi‐centre study

Abstract: Background: Lung metastasis (LM) status is critical for making treatment decisions in soft-tissue sarcoma (STS) patients, yet magnetic resonance imaging (MRI)-based prediction of LM in STSs has not been thoroughly investigated.Purpose: This study aimed to develop MRI-based radiomics models for identifying LM in STSs. Methods: We enrolled 122 STS patients from our hospital to form a primary cohort. Thirty-two patients from another hospital were included as an external validation cohort. All patients underwent T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In 14 (25%) studies [ 26 , 36 , 38 , 39 , 43 , 44 , 48 51 , 56 , 63 , 64 , 67 ], clinical validation was performed on an independent set of data from an external institution, namely the external test dataset. In 2 (4%) studies [ 22 , 33 ], both internal and external test datasets were used for clinical validation. The distribution of the employed clinical validation strategies among the included studies is shown in the bar plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In 14 (25%) studies [ 26 , 36 , 38 , 39 , 43 , 44 , 48 51 , 56 , 63 , 64 , 67 ], clinical validation was performed on an independent set of data from an external institution, namely the external test dataset. In 2 (4%) studies [ 22 , 33 ], both internal and external test datasets were used for clinical validation. The distribution of the employed clinical validation strategies among the included studies is shown in the bar plot in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, although the fully unsupervised h-RFs, the CAE clustering, and the HSCAE clustering exhibited c-indices lower than some previously published supervised models, they remained significantly better than Article random in both univariable and multivariable analyses accounting for cofounding covariables underscoring their intrinsic prognostic value for STS patients 7,14,18,[20][21][22] . Transcriptomics groups, while exhibiting weaker but significant associations with patient survivals, showed a substantial increase in prognostic performance (c-index = 0.709) when combined with HSCAE groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, a machine learning algorithm was built to predict the presence of lung metastasis at the time of soft tissue sarcoma tumor imaging. 52 Using radiomic features derived from contrast-enhanced fat-suppressed T1-weighted images of the soft tissue sarcoma and one semantic factor ("margin" ¼ well-or ill-defined) incorporated into a nomogram, an AUC of 0.843 (95% CI, 0.696-0.990) was demonstrated in the prediction of lung metastases in their external validation patient cohort. The authors concluded that their developed nomogram had potential value for preoperative prediction of lung metastasis status in soft tissue sarcomas, and it could offer essential information for clinicians in individualized treatment decision support for soft tissue sarcoma patients.…”
Section: Systemic Spread Of Diseasementioning
confidence: 99%